On the Place and Role of Astronomy and Astrophysics in the Emerging New Model of Education - Gheonjian, L. A.
Developing digital technologies as an evolutionary leap, we are clearly facing a crisis in traditional education system. We are close, or are already at the bifurcation point of techno-cultural evolution. Systems Theory (Bertalanffy (1968)) and the concept of Purposeful Systems (Ackoff & Emery (2009), Ackoff et al. (2006)) focuses on the design of a new model of education. The main difficulty of education is caused by contradictions between the fuzzy logic (Zadeh (1973)) of the humanities and the clear logic of natural sciences. Lingvistic variables of fuzzy logic, reflecting and classifying the multiplicity of objects and connections, allow fuzzy interpretation of reality. The concepts of number and measure achieve convergence in the identification of objects, in their study and in the creation of new objects of reality. Problems arise in the process of combining these two logics in education. Psychology, responsible for understanding of teaching-learning processes, encounters difficulties in solving these problems. Ethology, studying the social behavior of animals and humans, firmly argue that without solving the problems of education as a form of intelligence development, we become an endangered biological species if the environment we have created will be destroyed. We will return to the primitive, animal form of social behavior, since the form of social organization are transmitted genetically and lie deep in our subconscious (Dolnik (2009), Lorenz (1963, 1971)). The digitalization and standardization of education started replacing part, or all of the intelligence with the ability to use databases of ”recipes” for recognizing situations and appropriate behavior. Repetitions of each such recipe creates a fixed set of unconscious behavior (Uznadze (1995)) turning people into state of cybernetic organism. This perspective causes some blurred models of the present and gloomy forecasts and plans of social reconstruction. There is the need to clearly describe the reality in which our biological species exists and to transfer this knowledge into the process of education in the form of intellectual development. Astronomy and astrophysics have created the most fully formulated model of the Universe, that becomes an essential part of culture and practice. The analysis of the intellectual activity of our civilization identifies astronomers and astrophysicists as a special group of purposeful and advanced carriers of intellect whith the great potential for formation of a new model of education. The development of astronomy and astrophysics can be represented as a continuous process of transforming the concepts of fuzzy logic into constructing the model the Universe as observable, measurable and clearly described system. The specificity of the subject of study, the need to constantly develop complex specific technologies for remote research and the need to use the most advanced methods for describing, interpreting and understanding the results, created conditions for specific Cerebral Sorting (Saveliev (2016)) and formation of advanced intellectual, professional and social community. All significant results in General Psychology have been achieved in cooperation with exact and natural sciences. It is reasonable to offer astronomers and astrophysicists ideas explaining their intellectual activity and consistent with the concepts and ideas of General Psychology. This knowledge may became the part of activity technology and motivation to form a system based on astronomy and astrophysics as a model of cognition and education. Such a model based on General Psychological Theory of Set (Nadirashvili (2007), Uznadze (1995)) is proposed for discussion and use.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture